Dynamics and fragmentation mechanism of (C5H4CH3)Pt(CH3)3 on SiO2 surfaces - Muthukumar, Kaliappan; Jeschke, Harald O.; Valentí, Roser (Beilstein Journal of Nanotechnology, 2018)
The interaction of trimethyl(methylcyclopentadienyl)platinum(IV) ((C5H4CH3)Pt(CH3)3) molecules on fully and partially hydroxylated SiO2 surfaces, as well as the dynamics of this interaction were investigated using density functional theory (DFT) and finite temperature DFT-based molecular dynamics simulations. Fully and partially hydroxylated surfaces represent substrates before and after electron beam treatment and this study examines the role of electron beam pretreatment on the substrates in the initial stages of precursor dissociation and formation of Pt deposits. Our simulations show that on fully hydroxylated surfaces or untreated surfaces, the precursor molecules remain inactivated while we observe fragmentation of (C5H4CH3)Pt(CH3)3 on partially hydroxylated surfaces. The behavior of precursor molecules on the partially hydroxylated surfaces has been found to depend on the initial orientation of the molecule and the distribution of surface active sites. Based on the observations from the simulations and available experiments, we discuss possible dissociation channels of the precursor.
Keywords: deposition; dissociation; electron beam induced deposition (EBID); focused electron beam induced deposition (FEBID); precursor; trimethyl(methylcyclopentadienyl)platinum(IV) ((CH3-C5H4)Pt(CH3)3)